Arbetsterapeuters erfarenheter av teamarbete vid rehabilitering av personer med ryggmärgsskada - Fors Olsson, Anna; Olsson, Veronika (2015)
Objective: The aim of this study was to describe occupational therapists experience of team work in the rehabilitation of people with spinal cord injury. Methods: A qualitative approach was used. Sex therapists from northern Sweden were interviewed. All worked in teams with rehabilitation of people with spinal cord injury. Data were analyzed using a qualitative content analysis. Results: The results were divided into a main category: Teamwork is a must for working with rehabilitation of people with spinal cord injury and three sub-categories: client-centered team collaboration, structured team collaboration and occupational therapists responsibilities in the team. Conclusion: The study showed that teamwork is important in the rehabilitation of people with spinal cord injury. Client centering, communication, collaboration and logistical planning is described as key elements of team work. The study will bring knowledge for occupational therapists and other professionals who work in teams, since it describes the importance of team work in the rehabilitation of people with spinal cord injury. Further research is required because of limitations with the study. Validerat; 20150604 (global_studentproject_submitter)